Choice experiments and collaborative decisions on the uses and values of rivers. Issue 2 (2nd April 2016) - Sinner, Jim; Bell, Brian; Phillips, Yvonne; Yap, Michael; Batstone, Chris
ABSTRACT: There is growing interest in deliberative and collaborative approaches to environmental management and in obtaining information on values to inform these processes. We explore the question of when a discrete choice experiment (DCE) is most useful for policy formulation, through discussion of a DCE designed to identify public preferences for freshwater management. The study was conducted in a contested New Zealand policy context with a collaborative stakeholder group considering the uses and values of local rivers. Using a DCE, survey responses were collected and analysed to estimate public preferences for changes in river attributes. This produced informative results, but suffered from a limited sample and a decision not to use a focus group to aid survey design. The results were challenged by members of the stakeholder group on various grounds that went well beyond these limitations. The group was not ready to accept the DCE results as an input for decision-making, with one referring to the study as 'manufacturing consent'. For DCE to produce results that are accepted in contested policy contexts, it needs to be more integrated into the stakeholder engagement process. This has implications for moves towards greater use of collaborative decision-making for natural resource management.